POLA KOMUNIKASI KELUARGA ANTARA MENANTU DAN MERTUA YANG TINGGAL DALAM SATU RUMAH - Saro, Elisabeth; Ghofur, M. Abdul; Rakhim Syahida, Amanah (Jurnal Komunikasi Nusantara, 2019)
The study used qualitative research methods. The research is intended to know and understand in more detail related to the phenomenon of what is experienced by the subject to be investigated, through various data collection techniques conducted by researchers to obtain data on "Family Communication Patterns between Daughter-in-law and In-laws who live in one house in Bendrong Village Jabung District?. The problem is analyzed using the Rogers and Kincaid paradigms. The research method used was descriptive qualitative and the sampling technique used was puposive sampling by interviewing 6 informants in Bendrong village. Data collection taken using interview guides, observations and documentation. While data analysis is collecting data, reducing data, presenting data and drawing and conclusions. The results of the study revealed that where the pattern of communication between in-laws and in-laws often exchanges information, as shown in the chart above, where in-laws are usually the speakers or can be referred to as communicators, while the sons-in-law as recipients of messages or communicants, but usually often exchange positions within the period specific time and situation. Messages or information conveyed both by in-laws and in-laws are usually spoken directly or face to face or indirectly such as through social media mobile phones. In this case there is a reciprocal relationship between the two. Thus, the relationship between the daughter-in-law and the mother-in-law who tends to conflict will get worse if the two of them live together, because the high intensity of confusion results in a higher chance of friction.